Basic life support training programme in schools by school nurses: How long and how often to train?. Issue 13 (2nd April 2021) - Martínez-Isasi, Santiago; García-Suárez, Mario; De La Peña Rodríguez, Medea Aglaya; Gómez-Salgado, Juan; Fernández, Nélida; Méndez-Martínez, Carlos; Leon-Castelao, Esther; Clemente-Vivancos, Alvaro; Fernández-García, Daniel
Abstract: Background: Cardiopulmonary resuscitation (CPR) training in schools, despite being legislated in Spain, is not established as such within the subjects that children are taught in schools. Objective: to evaluate the acquisition of CPR skills by 11-year-old children after a brief theoretical-practical teaching programme taught by nurses at school. Methods: 62 students were assessed in a quasi-experimental study on 2 cohorts (51.4% of the sample in control group [CG]). In total, 2 sessions were given, a theoretical one, and a practical training for skill development in children, in which the CG performed the CPR in 2-minute cycles and the intervention group in 1-minute cycles. The anthropometric variables recorded were weight and height, and the variables compression quality and ventilation quality were recorded using the Laerdal ResusciAnne manikin with Personal Computer/Wireless SkillReport. Results: The assessment showed better results, in terms of BLS sequence performance and use of automated external defibrillator, in the CG and after training, except for the evaluation of the 10-second breathing assessment technique. The quality of chest compressions was better in the CG after training, as was the quality of the ventilations. There were no major differences in CPR quality after training and 4 months after the 1-minute and 2-minute training cycles. Conclusions: 11-year-old children do not perform quality chest compressions or ventilations but, considering their age, they are able to perform a BLS sequence correctly.